Perencanaan Stategis Sistem Informasi Administrasi di SLBN Nunumeu SoE Menggunakan Metode Ward and Peppard - Anjarwanti S. R. Suseno; Agustinus Fritz Wijaya (Journal of Computer and Information Systems Ampera, 2020)
Special education school is a school established by the government with a special concept for Children with Special Needs. In carrying out activities, there is an Administration section which is an important part of the process of activities at school, but there are obstacles, namely not being well systemed so that it creates difficulties in operating. In building a good system, it is necessary to have a Strategic Information System planning in advance, therefore this research was conducted. This research was conducted using the Ward and Peppard method and using the SWOT, Value Chain, and MCFarland Strategy analysis methods, with qualitative research methods, then providing output in the form of proposed applications to be considered in future application development in order to facilitate all activities in the administrative section of SLBN Nunumeu.